Sesame lignans increase sympathetic nerve activity and blood flow in rat skeletal muscles - Egawa, K; Horii, Y; Misonou, Y; Yamasaki, I; Takemoto, D; Ono, Y; Rogi, T; Shibata, H; Nagai, K (Physiological research, 2020)
Beneficial effects of sesame lignans, especially antioxidative effects, have been widely reported; however, its potential effects on autonomic nerves have not yet been investigated. Therefore, the current study aimed to investigate the effect of sesame lignans on the autonomic nervous system. The sympathetic nerve activity in rat skeletal muscle was measured using electrophysiological approaches, with blood flow determined using the laser Doppler method. Sesame lignans were administered intragastrically at 2 and 20 mg/kg, and after 60 min, the sympathetic nerve activity was observed to increase by 45.2% and 66.1%, respectively. A significant increase in blood flow (39.6%) was also observed for the 20-mg/kg dose when measured at 55 min after administration. These sympathomimetic effects were completely prevented by subdiaphragmatic vagotomy, and the increase in blood flow was eliminated in the presence of the beta2-adrenergic receptor inhibitor butoxamine. Thus, it is proposed that sesame lignans can increase the blood flow of skeletal muscle, possibly by exciting sympathetic nerve activity through the afferent vagal nerve.
Keywords: Lignans; lignany; rychlost toku krve; kosterní svaly; krysa rodu Rattus; hemodynamika; Animals; Sesamum; Blood Flow Velocity; sympatická vlákna postgangliová; Hemodynamics; mužské pohlaví; zvířata; Male; Sympathetic Fibers, Postganglionic; Rats; Muscle, Skeletal